Recovery of pad-free continence in elderly men does not differ from younger men undergoing robot-assisted radical prostatectomy for aggressive prostate cancer - Nyarangi-Dix, Joanne; Tosev, Georgi; Reimold, Philipp; Aksoy, Cem; Hatiboglu, Gencay; Teber, Dogu; Mansour, Josef; Radtke, Jan Philipp; Hohenfellner, Markus (World journal of urology, 2020)
To analyze urinary continence outcome following robot-assisted radical prostatectomy (RARP) for aggressive prostate cancer in men aged ≥ 70 and < 70 years.
Published online: 11 May 2019
Gesehen am 27.02.2020